Differential Accumulation and Middle East Wars: Beyond Neo-Liberalism - Shimshon Bichler; Jonathan Nitzan (Global Regulation. Managing Crises After the Imperial Turn, 2004)
It is popular these days to talk about the "discontent" of neoliberal globalization. This "discontent" is no longer the prerogative of intellectuals. Increasingly, it comes from below, with opposition from the grassroots. But there may be another type of discontent lurking behind the scenes. This other discontent comes from above. It is the discontent of the ruling class. In our opinion, the world may have reached a historical junction in which a significant part of the global ruling class has become discontented with neoliberalism. The purpose of this presentation is threefold: (1) to explain why the world's dominant capital groups have become discontented with neoliberal globalization; (2) to speculate on what may replace neoliberal globalization; and (3) to link this transition in the nature of accumulation to the new wars.
Keywords: 330; arms; accumulation; capital; capitalism; conflict; corporation; crisis; distribution; elite; energy; finance; globalization; growth; imperialism; GPE; liberalism; Middle East; military; national interest; neoliberalism; oil; OPEC; ownership; peace; power; profit; ruling class; security; stagflation; state; stock market; technology; TNC; United States; US; violence; war